THE INFLUENCE OF SOCIAL FACTORS ON WOMEN'S SELF-ESTEEM - Abdullaeva Nilufar (Bright Mind Publishing, 2026)
This article examines the influence of social factors on women's self-esteem from a social psychology perspective. Key factors such as family, gender stereotypes, media, and the professional environment are analyzed. It is argued that women's self-esteem is shaped by social norms and expectations internalized through socialization.
Keywords: Self-esteem, women, social factors, gender stereotypes, social environment.